2004
DOI: 10.1596/1813-9450-3381
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the International Mobility of Skilled Workers (1990–2000): Release 1.0

Abstract: In this paper, we provide new estimates of skilled workers' emigration rates for about 190 countries in 2000 and 170 countries in 1990, including both developing and industrial countries. Using various statistical sources, we revisit Carrington and Detragiache's measures by incorporating information on immigrants' educational attainment and country of origin from almost all OECD countries. Our database covers 92.7 percent of the OECD immigration stock. In absolute terms, we show that the largest numbers of hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(154 citation statements)
references
References 22 publications
2
140
0
7
Order By: Relevance
“…As a rule of thumb, remittances obtained from the BOP equal 1.5 times those obtained from the household survey, with a correlation of .90 (Acosta, Calderon Fajnzylber and Lopez, 2006a). Nevertheless, a given country may be an outlier, so one may check also with other sources, for example a comprehensive estimate of bilateral stocks of migrants for 226 countries and territories compiled by Global Trade Analysis Project (GTAP, 2005), the OECD's Database on Immigrants and Expatriates (OECD, 2005) containing detailed information on the foreign-born population for almost all member countries of the OECD, the Docquier and Marfouk (2004) as well as Beine, Docquier and Rapoport (2006) databases on migration by education (and age of entry) from developing countries to OECD countries or Bhargava and Docquier (2006) Database on the International Migration of Physicians. These figures should provide a first glance at the extent of migration.…”
Section: Gauging the Importance Of Migrationmentioning
confidence: 99%
“…As a rule of thumb, remittances obtained from the BOP equal 1.5 times those obtained from the household survey, with a correlation of .90 (Acosta, Calderon Fajnzylber and Lopez, 2006a). Nevertheless, a given country may be an outlier, so one may check also with other sources, for example a comprehensive estimate of bilateral stocks of migrants for 226 countries and territories compiled by Global Trade Analysis Project (GTAP, 2005), the OECD's Database on Immigrants and Expatriates (OECD, 2005) containing detailed information on the foreign-born population for almost all member countries of the OECD, the Docquier and Marfouk (2004) as well as Beine, Docquier and Rapoport (2006) databases on migration by education (and age of entry) from developing countries to OECD countries or Bhargava and Docquier (2006) Database on the International Migration of Physicians. These figures should provide a first glance at the extent of migration.…”
Section: Gauging the Importance Of Migrationmentioning
confidence: 99%
“…We then derive an empirical equation of remittances and estimate it on a large panel of developing countries. As a measure of the brain drain, we use the dataset by Docquier and Marfouk (2004) that in turn builds on the pioneering work of Carrington and Detragiache (2004). We find considerable evidence that the brain drain is associated with a smaller flow of remittances.…”
Section: Remittances and The Brain Drain *mentioning
confidence: 99%
“…Thanks however to the pioneering work of Carrington and Detragiache (1998) and the contribution of Docquier and Marfouk (2004), this gap is now being filled. Carrington and Detragiache (1998) rely on the 1990 US census to estimate the number of skilled migrants to the US from a large set of sending countries.…”
Section: Remittances and The Brain Drain: Econometric Evidencementioning
confidence: 99%
“…Instead, Nicholas P. Glytsos (2010), analyzing the case of Bulgaria and Albania, found that these countries were marked to a great extent by substantial volumes of highly educated population leaving the country. In fact, these two countries have also been analyzed earlier (Docquier & Marfouk, 2004) who calculated that skilled emigration rate in 2000 was 20% for Albania and 5.8% for Bulgaria.…”
Section: Literature Reviewmentioning
confidence: 84%